(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Ophelimus maskelli Ashmead (Hymenoptera, Eulophidae), invasive gall inducer on eucalypt trees, recently spread in Italy and many other Mediterranean countries, seriously damaging both adult trees and young plants in nurseries. Given the large extension of eucalypt afforested areas in Sicily (25,835 ha, the greatest of Italian regions), a biological control project has been undertaken in alliance with the Volcani Center of Bet Dagan (Israele) and the CSIRO of Canberra (Australia), to introduce natural enemies of O. maskelli. Therefore, Closterocerus sp. (Hymenoptera, Eulophidae), a thelytokous and endophagous parasitoid, has been selected to be introduced in Sicily. No-choice parasitization tests on alternative hosts, carried out in laboratory, excluded any possible non-target effects on autochthonous entomofauna. Closterocerus sp. was released in five sites, two of which being in the suburbs of Palermo and the others in eucalypt afforested areas in the province of Palermo, Trapani and Caltanissetta. It was already found in 4 out of 5 release sites about twenty days after its introduction, and within the following two months parasitization raised to 46.6% in one of these sites. Five months apart from the release date, Closterocerus sp. was found in all the five release sites and furthermore in five more areas 1-2 kilometres away from them, where the exotic parasitoid spontaneously spread. In all the suburban release sites parasitization now exceeds 95%, while ranges from 9.9 to 88.6% in the afforested release sites, where the parasitoid dispersal is probably higher. Moreover, Closterocerus sp. was found 5.6 km apart from the nearest suburban release site six months later. Whether recovered at the end of the winter, the exotic parasitoid can be considered a good biological control agent against O. maskelli, showing high specificity and a remarkable dispersal rate. Evaluation of more natural enemies of both O. maskelli and Leptocybe invasa Fisher & La Salle (Hymenoptera, Eulophidae), the other eucalypt exotic gall wasp, is yet in progress with the aid of Prof. Zvi Mendel (Volcani Center) and Dr. John La Salle (CSIRO).